Analisis Produktivitas Menggunakan Metode Objective Matrix (OMAX) dengan Pendekatan Root Cause Analysis (RCA) - Qipty Raihan Azizah; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is a firm that works in the steel and building construction industry. Throughout its manufacturing operations, the company has encountered ongoing difficulties in meeting production targets consistently, resulting in reduced productivity performance. This study aims to evaluate productivity levels through the Objective Matrix (OMAX) method, with the Analytical Hierarchy Process (AHP) applied to determine and prioritize the relevant productivity indicators. In addition, Root Cause Analysis (RCA) is employed to investigate the underlying factors contributing to the company's productivity issues. The results of the study show that productivity indicators fluctuated during the measurement period. October recorded the highest productivity level at a productivity index of 105%, while November recorded the lowest productivity level at -3%. The AHP weighting results showed that Ratio 1 and Ratio 5 had the highest weights, achieving the lowest performance compared to the other ratios. Based on the RCA analysis and the fishbone diagram, the causes of low productivity stemmed from human, machine, material, and working condition factors. The root causes were then analyzed using the 5 Whys method to determine proposed improvements aimed at increasing the company’s productivity